2014
DOI: 10.1371/journal.pone.0088358
|View full text |Cite
|
Sign up to set email alerts
|

Reading Direction and the Central Perceptual Span in Urdu and English

Abstract: BackgroundNormal reading relies on the reader making a series of saccadic eye movements along lines of text, separated by brief fixational pauses during which visual information is acquired from a region of text. In English and other alphabetic languages read from left to right, the region from which useful information is acquired during each fixational pause is generally reported to extend further to the right of each fixation than to the left. However, the asymmetry of the perceptual span for alphabetic lang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
52
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 41 publications
7
52
0
Order By: Relevance
“…Footnotes 1. It seems likely that this directional influence is reversed for languages read from right to left (e.g., Jordan, Almabruk, Gadalla, McGowan, White, Abedipour, & Paterson, 2014;Paterson, McGowan, White, Malik, Abedipour, & Jordan, 2014;Pollatsek, Bolozky, Well, & Rayner, 1981) although the precise parameters and nature of the left and right components of the perceptual span in such languages remain to be determined.…”
Section: Postview Effects In Reading 21mentioning
confidence: 99%
See 2 more Smart Citations
“…Footnotes 1. It seems likely that this directional influence is reversed for languages read from right to left (e.g., Jordan, Almabruk, Gadalla, McGowan, White, Abedipour, & Paterson, 2014;Paterson, McGowan, White, Malik, Abedipour, & Jordan, 2014;Pollatsek, Bolozky, Well, & Rayner, 1981) although the precise parameters and nature of the left and right components of the perceptual span in such languages remain to be determined.…”
Section: Postview Effects In Reading 21mentioning
confidence: 99%
“…It seems likely that the rightward perceptual span for rightwards-read languages reflects forward-directed processes that are aligned to the general direction of reading (e.g., Jordan, Almabruk, Gadalla, McGowan, White, Abedipour, & Paterson, 2014;Paterson, McGowan, White, Malik, Abedipour, & Jordan, 2014;Pollatsek, Bolozky, Well, & Rayner, 1981). 1 Indeed, acquiring information from words to the right of each fixation is likely to be driven by attentional influences and by the importance of previews of words that have yet to be identified, both of which appear to contribute considerably to efficient and effective reading (e.g., Rayner, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the constraint of the attentional window by spatial deployment of finite attentional resources (Jordan et al, 2013;Miellet, O'Donnell, & Sereno, 2009;Paterson et al, 2014), it may well be expected that the extent of these attentional windows would be constricted by the conflict in attentional deployment when reading scrolling text, reducing parafoveal availability of text and thus average progressive saccade length. This may occur via increased foveal processing difficulty: in other situations, an increase in foveal load has been proposed to reduce the rightward extent of the attentional window (Henderson & Ferreira, 1990;White, Rayner, & Liversedge, 2005).…”
Section: Horizontally Scrolling Textmentioning
confidence: 99%
“…The perceptual span is also related to the written characteristics of the language that is read. For example, the perceptual span of Israeli or Urdu readers is asymmetric to the left because the reading direction of these languages is leftwards (Paterson et al, 2014;Pollatsek, Bolozky, Well, & Rayner, 1981).…”
Section: Perceptual Spanmentioning
confidence: 99%